-5(3t-2)+7t=4t-9

Simple and best practice solution for -5(3t-2)+7t=4t-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(3t-2)+7t=4t-9 equation:


Simplifying
-5(3t + -2) + 7t = 4t + -9

Reorder the terms:
-5(-2 + 3t) + 7t = 4t + -9
(-2 * -5 + 3t * -5) + 7t = 4t + -9
(10 + -15t) + 7t = 4t + -9

Combine like terms: -15t + 7t = -8t
10 + -8t = 4t + -9

Reorder the terms:
10 + -8t = -9 + 4t

Solving
10 + -8t = -9 + 4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4t' to each side of the equation.
10 + -8t + -4t = -9 + 4t + -4t

Combine like terms: -8t + -4t = -12t
10 + -12t = -9 + 4t + -4t

Combine like terms: 4t + -4t = 0
10 + -12t = -9 + 0
10 + -12t = -9

Add '-10' to each side of the equation.
10 + -10 + -12t = -9 + -10

Combine like terms: 10 + -10 = 0
0 + -12t = -9 + -10
-12t = -9 + -10

Combine like terms: -9 + -10 = -19
-12t = -19

Divide each side by '-12'.
t = 1.583333333

Simplifying
t = 1.583333333

See similar equations:

| 3x-7+6x+2= | | -5(3t-2)+4t=8t-6 | | -14+n=-11 | | 2X^2+19x+80=0 | | 54=-3/4p | | 9x+y=-26 | | f(0)=(2x^(2)-10)/(7x-5) | | 1.21x=3.2 | | 3.2x=1.21 | | X+-11=-12 | | -2(a+3)-5=-4(a-2)+1 | | 3(7m+4)+5=6(5m-3)-4m | | -21+8+3x= | | 5(2c+4)+4c=8(3c-2)+6 | | -1=3t-19 | | 7=w-(-7) | | 4(x+1)+2x=3(x+5)+1 | | 4+5a=-16 | | 4a-2c/2 | | 2(3a+5)+4=3(3a+2)-a | | 3(4m+5)+6m=8(3m-2)-7m | | 3(4m+5)+6m=5(6y+3)-8 | | 3x+40=320 | | 4x^2-x^2-81=0 | | 10(3a-5)+8=9(4a+3)-5a | | x^2-2x-74=0 | | 4(7y+2)+y=5(6y+3)-8 | | 6(2w+8)+3w=2(10w-5)-4w | | 8(4n+3)-5=7(5n-4)-2n | | 4(2m+3)+4=2(5m+4)-m | | 2(x-4)=m(1+x) | | 2(12+R)-(R+3)=8(2-3R)-3(5-6R) |

Equations solver categories